PENGARUH PENDEKATAN BANTUAN LANGSUNG TERHADAP KETERAMPILAN HANDSTAND - ., Zulbahri (Edu Research, 2016)
Based on the field observation showed that generally students training’s departement of the Faculty of Sport Science Padang State University have still lack of handstand skill especially in the course of basic gymnastics in semester januari - june 2013. The purposed of this study is to find out wether direct spotting will have a significant effect to handstand.The population in this study were all students training’s departement of the Faculty of Sport Science Padang State University were amount 110 people. Random sampling was used to obtain 12 people samples of 10-15% of the total population. The data of the handstand were collected by observation sheet tables of assessment by the jury or the assessment team. The results of the analysis of the data showed that There is an effect of direct spotting toward handstand on students training’s departement of the Faculty of Sport Science Padang State University t test (83.9)> t (1.796).